PERSEPSI GURU TERHADAP PEMBELAJARAN APRESIASI CERITA PENDEK BERMUATAN PENDIDIKAN TOLERANSI - Main Sufanti; Nuraini Fatimah; Sa'diyah Nur'aini; Danang Tri Atmojo (Kajian Linguistik dan Sastra, 2018)
The objectives of study are: (1) to describe the character education that the teacher prioritized in learning short story appreciation, (2) the teacher's perception of the effectiveness of integrating tolerance education in short story learning, and (3) the teacher's perception of short story teaching materials containing tolerance education. This research is a qualitative descriptive study. The data are information or statements of teachers about tolerance education in short story appreciation learning. The data was taken from a data source, namely the Indonesian Language Subject teacher at SMA in Surakarta. Data collection techniques are interviews and questionnaires. Method triangulation techniques as data validation techniques. Interactive analysis techniques as data analysis techniques. The results of this study are as follows. (1) The character that is important to the teacher in learning short stories varies. Overall there are 19 characters that the teacher places importance on teaching. Each teacher attaches importance to 3-10 characters. The characters most chosen by teachers are tolerance (78%), responsibility (67%), and independence and honesty (44% each). (2) All teachers stated that effective tolerance education was integrated in short story appreciation learning, all teachers considered it important to integrate tolerance education into short story learning, and the majority of teachers (67%) stated that tolerance education was urgent to be implemented. (3) In connection with teaching materials, 78% of teachers stated that they had planned short story learning with the character education of tolerance, 78% of teachers had found short stories teaching materials containing education tolerance, and all teachers were willing to use short stories teaching material with tolerance education. Keywords: perception, learning, short story appreciation, tolerance